G119 A pilot multi agency approach to young people with persistent physical symptoms. (24th May 2017) - Street, K; Pales, J; Lee, A; Burrows, J; Bowman, P; Jones, H; O'Brien, E
Abstract : Background/aims: Young people with Persistent Physical Symptoms (PPS) that reduce function and school attendance are worrying. Many have repeat admissions/appointments, unnecessary investigations/treatments. Local data showed 4% of inpatients/ outpatients<18 years in our district general hospital have PPS. Data from education welfare services (EWS) showed 10% of <85% school attenders known to local paediatricians with PPS. Paediatrics, Child and Adolescent Mental Health Services (CAMHS) and EWS committed to a 12 month pilot of joint working cases to assess impact and inform service development. Methods: Since June 2016 a weekly, hour long meeting with psychiatrist, CAMHS worker, psychologist and EWS inclusion officer, facilitated by paediatrician. Allied health professionals join where appropriate. Cases presented by managing paediatrician. All planned input provided within existing resource plus additional 3 hr/week of CAMHS therapist and paediatric staff grade providing joint appointments where appropriate. Databases, case studies, questionnaires (SDQ, RCADS, DAWBA, session rating scales), focus groups provided outcome data. Results: 32 cases discussed in 5 months. Symptoms included abdominal/joint/muscle pains, headache, fatigue, acute behavioural disturbance, breathing difficulty. Median age 15 (4–18), girls: boys 2:1. 5 were repeat attending inpatients, 27 outpatients. Previous investigation included bloods, neurophysiology, medical imaging. 4 were out of school, 13<85% attendance. Outcomes ranged from further information gathering and rediscussion (6), signposting school/community services (4), joint paediatric/ CAMHS appointments (9), CAMHS assessment/input (10), allied health professional input (3). 18 were discharged from medical follow up, no further admissions. 2 education referrals for out of school provision reversed and successfully reintegrated, overall improved school attendance in cohort. Qualitative feedback from professionals involved showed better understanding of PPS and mental health comorbidities. Paediatricians reported change in practise to reduce investigations/follow up and raising psychological aspects of symptoms earlier. Feedback from young people/ families was positive. Conclusion: Joint working between physical/mental health/education services is an acceptable and effective way of managing young people with PPS and can reduce hospital admissions/ appointments, investigations, improve school attendance/reintegration. Mental health comorbidity is common. Poor school attendance/attainment and mental illness is associated with long term burden on public services. Additional resource is needed to provide joined up services offering assessment/support for PPS in young people and needs to be recognised by commissioners as investment to save.